Pemanfaatan Media Games TGT dalam Model Kooperatif pada Pembelajaran SKI di Madrasah Ibtidaiyah - Fairuz Zuhro Nabila; Lulu Salama Wardani; Muhamad Kurofi; Nina Miratus Saadah; Putri Hasna Huwaida; Sheilla Pramudita; Yulia Rahmawati; Dian Rifiyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article reviews the contribution of game-based media integrated with the Teams Games Tournament (TGT) model to the teaching of Islamic Cultural History (SKI) in Madrasah Ibtidaiyah (MI) schools. A qualitative design employing a meta-analysis approach was adopted, involving the collection and examination of scholarly articles published between 2015–2025, sourced via Google Scholar. Rather than performing a combined statistical analysis, the authors descriptively reviewed and compared the findings to identify recurring patterns across various contexts. The resulting synthesis reveals a consistent trend: classes integrating TGT with game-based media generally reported improvements in both learning outcomes and student engagement compared to conventional methods. The tournament phase, in particular, enlivened the classroom atmosphere and fostered more active participation. Consequently, the gathered evidence suggests that TGT supported by game-based media is a viable instructional option for SKI at the MI level, provided that teachers are prepared to effectively manage the format.